Thermal performance of cement-based composite tiles reinforced with selected natural fibres (2020)
This study was designed to investigate the thermal performance of cement-based composite tiles reinforced with suitably processed sawdust of Gmelina arborea, pineapple leaves and corn husks. Standard procedures were followed in the production and testing of the tiles. The properties evaluated include thermal conductivity, resistivity and diffusivity. These properties were compared with conventional and commercially available roofing sheets. Insulating properties and hence thermal comfort improved with increase in fibre contents in the composites. Tiles reinforced with sawdust performed best followed by corn husks and pineapple leaves, in that order. Fibre reinforced cement-based composite tiles presented better thermal performance than conventional and commercially available roofing materials. The results obtained were similar to those of ceramics and asbestos roofing tiles. However, the use of asbestos tiles had been banned in advanced countries for health reasons. The selected natural fibre composite tiles are therefore considered as suitable building materials for housing in terms of thermal comfort when compared with the conventional roofing materials for the tropics.